PENGARUH CITRA MEREK DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS PELANGGAN (Studi Pada Anggota Komunitas Sepeda Motor Honda Vario 125cc di Surabaya) - DWI WARUSMAN, JUWONO (Jurnal Ilmu Manajemen (JIM), 2016)
Motorcycles Honda Vario 125cc has an elegant design and fashionable, and has details of the quality that is superior compared to other brands. This is supported by the Surabaya has several places of purchase and ordering Honda motorcycles there are showrooms, dealers and authorized workshops and non official. This study aims to analyze and discuss the influence of brand image and brand trust on customer loyalty. The population in this study were respondents who use motorcycles 125cc Honda Vario, respondents aged 18-57 years and previously had a 125cc Honda Vario. In this study, researchers used 220 samples. Methods of data collection in this study is the observation, documentation and questionnaires. The sampling method is particularly nonprobability sampling using purposive sampling. Measuring instrument used is multiple linear regression. The results show that the partial image of the brand influence on consumer loyalty and brand trust also affect customer loyalty. Keywords: brand image, brand trust, customer loyalty.